2019
DOI: 10.3390/genes10070483
|View full text |Cite
|
Sign up to set email alerts
|

Host-Associated Bacterial Succession during the Early Embryonic Stages and First Feeding in Farmed Gilthead Sea Bream (Sparus aurata)

Abstract: One of the most widely reared fish in the Mediterranean Sea is Sparus aurata. The succession of S. aurata whole-body microbiota in fertilized eggs, five, 15, 21 and 71 days post hatch (dph) larvae and the contribution of the rearing water and the provided feed (rotifers, Artemia sp. and commercial diet) to the host’s microbiota was investigated by 454 pyrosequencing of the 16S rRNA gene diversity. In total, 1917 bacterial operational taxonomic units (OTUs) were found in all samples. On average, between 93 ± 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 66 publications
9
56
0
Order By: Relevance
“…The water microbiome of shponds were signi cantly distinct and more diverse than the skin and gill microbiomes of both sh, regardless of their age. It is known that free-living microbial communities retain higher richness than host-associated communities [31], with many studies showing a higher bacterial diversity in water relative to sh skin [28,30,36,[58][59][60], gills [14,36], gut [7,15,18,21,61], stomach [36], hindgut [36] and whole larvae [22]. Although some studies in sh have shown that the microbial communities found in the water tend to be recovered in the larval gut microbiome [17,21], others have also shown that water microbiomes do not in uence directly the microbiomes of sh mucosa [7, 8, 13-15, 18, 19, 22, 28, 30, 34, 36, 58-60, 62, 63].…”
Section: Fish and Water Microbiome Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations
“…The water microbiome of shponds were signi cantly distinct and more diverse than the skin and gill microbiomes of both sh, regardless of their age. It is known that free-living microbial communities retain higher richness than host-associated communities [31], with many studies showing a higher bacterial diversity in water relative to sh skin [28,30,36,[58][59][60], gills [14,36], gut [7,15,18,21,61], stomach [36], hindgut [36] and whole larvae [22]. Although some studies in sh have shown that the microbial communities found in the water tend to be recovered in the larval gut microbiome [17,21], others have also shown that water microbiomes do not in uence directly the microbiomes of sh mucosa [7, 8, 13-15, 18, 19, 22, 28, 30, 34, 36, 58-60, 62, 63].…”
Section: Fish and Water Microbiome Comparisonsmentioning
confidence: 99%
“…In piscine hosts, most of the microbiome studies related to the effects of age are focused on the gut microbiomes [12][13][14][15][16][17][18][19][20][21][22]. Some of these studies showed that microbial communities in the surrounding waters in uence the gut microbiome during early life stages, which becomes increasingly unique with age [17,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its economic value, many studies on gilthead sea bream intestinal microbiota have been conducted. These studies were mainly focused on de ning baseline populations [35][36][37] or changes induced by diet [18,[38][39][40][41][42][43][44] or environmental conditions [45]. The microbiota is composed of very dynamic populations that are affected by different factors [18,36,[53][54][55]42,[46][47][48][49][50][51][52] such as diet, season, habitat, rearing density, age, sex and genetic background, the focus of the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its economic value, many studies on gilthead sea bream intestinal microbiota have been conducted. These studies were mainly focused on de ning baseline populations [35][36][37] or changes induced by diet [18,[38][39][40][41][42][43][44] or environmental conditions [45]. The microbiota is composed of very dynamic populations that are affected by different factors [18,36,42,[46][47][48][49][50][51][52][53][54][55] such as diet, season, habitat, rearing density, age, sex and genetic background, the focus of the current study.…”
Section: Introductionmentioning
confidence: 99%